Printed circuit board substrates derived from lignocellulose nanofibrils for sustainable electronics applications - Yuliia Dudnyk; Pavel Kulha; Václav Procházka; Gustav Nyström; Thomas Geiger (Scientific Reports, 2025)
Abstract This study investigates lignocellulose nanofibrils (LCNF) as a sustainable alternative material for printed circuit board (PCB) substrates, demonstrating an application through the development of an eco-friendly computer mouse demonstrator. LCNF is derived from lignin-rich cellulose pulp, a side stream product of biorefinery processes, combining the natural strength of cellulose fibrils with lignin to enhance mechanical and electrochemical properties. The research outlines the process of fibrillating lignin-rich cellulose pulp at 10 kW/h per kg into LCNF, followed by thermal and pressure treatment (at Δp = 50 – 1500 kN, ΔT = 30 – 120 °C) to achieve a rigid PCB substrate. Comprehensive characterization of the LCNF substrate included assessments of its mechanical properties (flexural and tensile testing), dimensional stability, electrical properties, surface uniformity and thermal conductivity. The LCNF PCB was integrated in a computer mouse demonstrator featuring inkjet printing of circuit layouts and electronic component assembly, while the mouse housing was designed and 3D-printed using eco-friendly Wood-PLA filament. Electrical properties characterization of the printed circuit and resulting functionality of the computer mouse showcases a sustainable approach to eco-electronics using wood-derived materials. This study underscores the potential of wood-derived nanomaterials like LCNF to reduce electronic waste (e-waste) associated with conventional PCB materials and promote the development of a more eco-friendly electronics, contributing to sustainable, high-performance ecoPCBs and advancing green technology.